Analogue feed‐forward carrier recovery for millimetre‐wave broadband wireless links. Issue 5 (21st February 2020) - Harati, Parisa; Kallfass, Ingmar
Abstract : An analogue modulation‐type independent feed‐forward carrier recovery approach for broadband wireless communication systems is introduced in this work. The focus is on the deliberately increased local oscillator (LO) signal feed‐through to the radio frequency (RF) port of the up‐converter in a direct conversion transmitter (TX). The strong LO feed‐through is used at the receiver (RX) side to demodulate the RF signal. The heart of the carrier recovery block is a narrowband bandpass filter (BPF) and a frequency divider‐by‐ n operated in injection‐locking mode to the strong LO feed‐through. The proposed method is investigated through circuit level simulations; while its feasibility is examined via the successful demodulation of complex data with various modulation types up to 8 Gbps for an E‐band front‐end. This method can be used for transceivers working at high carrier frequencies as far as the realisation of frequency divider circuits and narrowband BPFs is technically feasible.